Profile of Colonoscopy Findings: A single Centre Experience - Kidwai, Roman; Sharma, Anup (Journal of Nepalgunj Medical College, 2018)
Background: About 30% of patients presenting to surgical outpatient department has lower gastrointestinal (LGI) symptoms. Colonoscopy is a low risk and at the same time investigation of choice in these patients which allows visualization of the entire colon and the terminal portion of ileum. This study was done to evaluate the role of colonoscopy. Methods: This was an observational, hospital based study from February 2014 to March 2018, carried out at Nepalgunj Medical College and Teaching Hospital. Results: 245 patients underwent colonoscopy, among them 62.85% were male and 37.14% were female with the M:F ratio being 1.6:1. The youngest patient undergoing colonoscopy was 21 and the eldest was 78 with the mean age being 53.6±12. The common indications were per rectal bleeding (49.38%), alteration in bowel habit (40.49%), and constipation (13.46%). In 85.71% patients entire large bowel could be visualized. In 21.22% no abnormality was detected. Haemorrhoids (27.34%) were the most common findings and then nonspecific inflammatory bowel diseases (17.55%), colorectal polyps (15.51%) and colorectal cancers (14.28%). Biopsy was done in 39.51% patients and the most common finding was nonspecific inflammatory bowel disease, 36.08% had adenocarcinomas and rest had ulcerative colitis, juvenile and hamartomatous polyps. Conclusion: Colonoscopy is a safe and effective investigation in diagnosing as well as managing the patients with LGI symptoms.